Clonagem e expressão da toxina TX3-1 do veneno da aranha phneutria nigriventer - Andrea Cristina Gomes Pires (2008)
The toxin Tx3-1 purified from the spider venom Phoneutria nigriventer is a blocker of potassium channels with great pharmacological potential. However the purification of the toxin from Phoneutria nigriventer crude venom is a long and expensive process. The objective of this work was standardize techniques of molecular biology that would allow the expression and purification in large scale of functional recombinant Tx3-1.We cloned and expressed the toxin Tx3-1 tagged to the C-terminus of the maltose binding protein (MBP) in the cytoplasm of E. coli BL21. The hybrid protein purification was performed by affinity chromatography (amylase column). After purification, MBP-TX3-1 was cleaved by Factor Xa and recombinant Tx3-1 was purified by gel filtration using Superdex 75 column in FPLC system. Both, fusion protein MBP/Tx3-1 and recombinant Tx3-1 reacted with anti-Phoneutria nigriventer venom antibodies.The biological activity of recombinant toxin Tx3-1 was tested in biological assays and compared to native toxin biological activity. In experiments using rats cardiomyocytes, recombinant Tx3-1 toxin was able to increase the calcium transient in 20%, similarly to native toxin. Treatment of isolated rat hearts and atriums with recombinant Tx3-1, and native toxin, led to decrease in arrhythmia. These data suggest that the recombinant and native Tx3-1 probably present the same three-dimensional structure and function. These results open up the possibility of using the recombinant Tx3-1 to determine the molecular structure and action mechanisms of Tx3-1. Moreover, the recombinant protein enables the possibility of using the toxin Tx3-1 as a therapeutic drug for prevention and treatment of hearts diseases.